2021
DOI: 10.1096/fj.202001812rr
|View full text |Cite
|
Sign up to set email alerts
|

Targeted overexpression of PPARγ in skeletal muscle by random insertion and CRISPR/Cas9 transgenic pig cloning enhances oxidative fiber formation and intramuscular fat deposition

Abstract: Peroxisome proliferator-activated receptor gamma (PPARγ) is a master regulator of adipogenesis and lipogenesis. To understand its roles in fiber formation and fat deposition in skeletal muscle, we successfully generated muscle-specific overexpression of PPARγ in two pig models by random insertion and CRISPR/Cas9 transgenic cloning procedures. The content of intramuscular fat was significantly increased in PPARγ pigs while had no changes on lean meat ratio. PPARγ could promote adipocyte differentiation by activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 78 publications
(83 reference statements)
1
28
0
Order By: Relevance
“…Similarly, diabetes, age, and fatty acid have been reported to increase the expression of TLR4 in skeletal muscle. The elevated TLR4 in skeletal muscle might be attributed to the increased intramuscular fat deposition induced by diabetes, age, and fatty acid. In accordance, we found that TLR4 expression was positively correlated with the proportion of type I muscle fibers, which contain more intramuscular fat deposition. , …”
Section: Discussionsupporting
confidence: 65%
“…Similarly, diabetes, age, and fatty acid have been reported to increase the expression of TLR4 in skeletal muscle. The elevated TLR4 in skeletal muscle might be attributed to the increased intramuscular fat deposition induced by diabetes, age, and fatty acid. In accordance, we found that TLR4 expression was positively correlated with the proportion of type I muscle fibers, which contain more intramuscular fat deposition. , …”
Section: Discussionsupporting
confidence: 65%
“…As a master regulator of adipogenesis, Pparγ regulates many adipocyte genes involved in lipid metabolism and energy balance ( Desvergne and Wahli 1999 ). Severe lipoatrophy and metabolic disturbance resulted from Pparγ knockout in mice ( Jones et al, 2005 ; Wang et al, 2013 ) and overexpression of Pparγ in the mouse and pig resulted in increased intramuscular fat with an increased expression of adipogenic markers ( Ma et al, 2015 ; Gu et al, 2021 ). These genetic models suggest that the ectopic expression of Pparγ in skeletal muscles enhanced lipid accumulation and adipogenic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Recent efforts of exogenes KI at Rosa26 locus by CRISPR/Cas9, healthy and tasty pork could also be resulted [ 68 , 69 ]. You et al [ 68 ] generated dual, Fat1 and IGF-1 , transgenic (TG) pigs that could provide pork with a significantly higher ω-3 polyunsaturated fatty acid (PUFA) level and a significantly lower ratio of ω-6 PUFA/ω-3 PUFA.…”
Section: Application Of New Breeding Technology In Pig Productionmentioning
confidence: 99%
“…You et al [ 68 ] generated dual, Fat1 and IGF-1 , transgenic (TG) pigs that could provide pork with a significantly higher ω-3 polyunsaturated fatty acid (PUFA) level and a significantly lower ratio of ω-6 PUFA/ω-3 PUFA. Gu et al [ 69 ] generated TG pigs carrying muscle-specific overexpression of peroxisome proliferator-activated receptor gamma2 (PPARγ2), which significantly increased intramuscular fat content while maintaining carcass lean ratio. Although, KI the PPARγ2 gene is considered TG in pigs, yet, both sequences of promoter and PPARγ2 gene are based on pig genome [ 68 ] and thus the transgenes are “safe-harbored” in Rosa26 locus, making the pork safe as the ordinary.…”
Section: Application Of New Breeding Technology In Pig Productionmentioning
confidence: 99%